A Novel Hybrid Secure Method Based on DNA Encoding Encryption and Spiral Scrambling in Chaotic OFDM-PON - Yaoqiang Xiao; Yating Chen; Caixia Long; Jin Shi; Jie Ma; Jing He (IEEE Photonics Journal)
This paper proposes a novel hybrid secure method based on improved deoxyribonucleic acid (DNA) encoding encryption and spiral scrambling in chaotic OFDM-PON for enhancing the physical-layer security. In the improved DNA encoding encryption, the odd-even cross-bit DNA encoding, base scrambling and base-level substitution are determined by chaotic sequences. For each binary and base, the selected encoding rules and base scrambling methods are dynamically changing, which enhances the robustness against malicious attacks by attackers. In the spiral scrambling process, the QAM symbol matrix is divided into several blocks, and these blocks are scrambled. In the scrambling of the plural matrix, the position where the spiral starts and the orientation and direction of the traversal are also controlled by the chaotic sequences. By employing DNA encoding encryption and spiral scrambling, a key space of $\sim \!{10^{135}}$ can be achieved in the multi-fold encryption of the proposed scheme, which can improve the physical-layer security. The encrypted 16-QAM OFDM data are successfully transmitted over a 60-km SSMF in OFDM-PON. The simulation results demonstrate that it has better BER performance at the BER of ${10^{ - 3}}$ than other schemes. The proposed encryption method can effectively protect data from attacks by eavesdroppers or illegal users.